PU.1 upregulation is linked to improved prognosis in non-small cell lung cancer - Hohenberger, Katja; Trufa, Denis I.; Hartmann, Arndt; Mittler, Susanne; Trump, Sonja; Sirbu, Horia; Finotto, Susetta (Frontiers in Immunology, 2025)
BackgroundLung cancer is one of the most common types of cancer, which can currently be cured only partially. Even though the function of the transcription factor PU.1 as an oncogene has already been investigated in detail in various studies, its precise function and regulatory mechanisms in non-small cell lung cancer (NSCLC) remain to be fully elucidated.MethodsPatients with NSCLC and healthy controls were recruited at the Department of Thoracic Surgery of the University Hospital Erlangen. Tissue samples were dissected from patients who underwent lung tumor surgery and blood samples were collected from all participants.ResultsIn this study, we showed that the expression of PU.1 was increased both in the blood and in the tumor region of the lung of patients with NSCLC. On a more detailed analysis, PU.1 was found increased the most in CD56dim natural killer cells (NK cells). Furthermore, we demonstrated an increased cytotoxic potential for PU.1 expressing cells as well as improved overall and recurrence-free survival for patients with a higher expression of PU.1, suggesting a beneficial role for PU.1 in NSCLC.ConclusionHigh expression of PU.1 associated with NK cells could lead to a beneficial outcome and survival of NSCLC patients.